2021
DOI: 10.3390/en14030608
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Deep Learning Techniques for Forecasting Energy Use in Buildings

Abstract: Buildings account for a significant portion of our overall energy usage and associated greenhouse gas emissions. With the increasing concerns regarding climate change, there are growing needs for energy reduction and increasing our energy efficiency. Forecasting energy use plays a fundamental role in building energy planning, management and optimization. The most common approaches for building energy forecasting include physics and data-driven models. Among the data-driven models, deep learning techniques have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 91 publications
0
30
0
Order By: Relevance
“…ML offers several opportunities for problems related to monitoring of operations and optimisation. However, it has become increasingly clear that advances in DH-related ML research have a disproportionate focus on some problem areas, specifically forecasting [15][16][17][18], while missing out on several interesting problems, e.g., substation heat transfer, occupancy comfort, etc.…”
Section: Motivation and Objectivementioning
confidence: 99%
See 3 more Smart Citations
“…ML offers several opportunities for problems related to monitoring of operations and optimisation. However, it has become increasingly clear that advances in DH-related ML research have a disproportionate focus on some problem areas, specifically forecasting [15][16][17][18], while missing out on several interesting problems, e.g., substation heat transfer, occupancy comfort, etc.…”
Section: Motivation and Objectivementioning
confidence: 99%
“…To understand existing literature reviews in this area, we provide an overview of the knowledge gaps identified in various studies, the types of ML models reported, datasets employed and building characteristics (features) studied. Most research articles on the application of ML in DH have occurred in the last 10 years [7,15,18]. Each of the review studies addressed different research gaps, considered research articles over different time periods and considered various building types.…”
Section: Highlights Of Existing Literature Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep learning techniques are a solution that is becoming more and more popular in recent years for BEMS. One interesting application is the forecasting of the energy consumption in buildings in order to implement adapted mechanisms to optimize the energy management [95]. The BEMS based on MAS have also combined some DL techniques, for making agents more adaptative and intelligent.…”
mentioning
confidence: 99%